Cricoid Ossification Mimicking an Esophageal Foreign Body: A Victim of Overdiagnosis - Rohit Bhardwaj; Isha Preet Tuli; Mohamed Shareef PK; Ankur Gupta; Saurabh Makkar (Dubai Medical Journal)
Laryngeal cartilages undergo ossification, usually after the third decade of life. Variations exist in the extent and age of onset of ossification. Radiologically, these ossified cartilages may mimic an aerodigestive tract foreign body. We present an unusual case where the ossified cricoid cartilage masqueraded as a fish bone in the aerodigestive tract. A 48-year-old male patient presented to us with a foreign body sensation and throat pain after consuming fish. We found no fish bone on endoscopic laryngopharyngeal assessment but noted a linear opacity against the C-6 vertebral body in the aerodigestive tract on a lateral X-ray film of the neck. Rigid esophagoscopy also did not reveal any foreign object, but a computed tomography (CT) scan showed a linear hyperdensity in the wall of the aerodigestive tract, against the C-6 vertebral body, due to linear ossification in the midline of the cricoid lamina posteriorly. The patient’s symptoms improved within 1 week of anti-reflux medications, and he remains asymptomatic. It is possible to encounter such rare cases of cartilage ossification while dealing with foreign body aerodigestive tract in adult patients in clinical practice. Proper assessment using CT scan prevents unnecessary procedures and anxiety to the patient.